Analysis of Organizational Culture at Bank Mandiri Taspen KCP Sumedang - Amanda, Helles; Prastiono, Megan; Hidayat, Gustina (Journal of Bussines Management Basic, 2025)
The core of the problem in this research is that the organizational culture at Bank Mandiri Taspen KCP Sumedang has not been optimal in terms of self- awareness, aggressiveness, personality, performance and team orientation. This study aims to determine the implementation of organizational culture and efforts to improve organizational culture at Bank Mandiri Taspen KCP Sumedang. This study uses qualitative research methods, data collection techniques, namely observation (observation), interviews (interviews), and documentation. The sampling technique is purposive sampling, research informants as many as 8 people. The analysis technique is data collection, data reduction, data display and conclusions drawing/ verification. The results of the study explain that the analysis of organizational culture at Bank Mandiri Taspen KCP Sumedang is 1) self- awareness, employees feel satisfied with working and can meet the targets of a company. 2) aggressiveness, employees and members of the organization are always full of initiative. 3) personality, employees really appreciate, respect and serve customers because they work in the service sector and are oriented towards customer satisfaction as a profit center. 4) performance, employees always prioritize quality in completing their work in order to achieve the targets of a company. 5) team orientation, employees in every task and work team problem are always resolved properly and always consult their superiors. for Bank Mandiri Taspen KCP Sumedang in order to implement the values that guide human resources in carrying out their obligations and behavior within the organization